Component-based light-rail modeling in discrete event systems specification (DEVS). (December 2015) - Huang, Yilin; Seck, Mamadou D; Verbraeck, Alexander
Rail modeling and simulation is an effective decision support instrument for planning and designing complex rail infrastructures and operations. To successfully support these activities at a large scale, the simulation model should be sufficiently detailed and yet be computationally efficient. This poses a set of challenges pertaining to the design of the models. In this paper, we propose a component-based light-rail modeling and simulation library in the discrete event system specification (DEVS) formalism. The proposed library is described in detail and is shown to be efficient and scalable. We conclude the paper by offering a set of good design principles derived from this experience, which are also relevant to other types of large-scale infrastructure system simulation model design.